The development of synthetic peptidolipids, glycolipids and other lipid-linked structures to create designer red cells - Henry, S; Bovin, N (John Wiley & Sons, 2008)
Background: Red cells used in immunohematology assays are restricted by their natural phenotype and membrane characteristics. More recently a technology has been developed which allows for the attachment of a large variety of specific carbohydrates, peptides and other structures to the surface of cells – known as FSL cell surface coating (KODETM technology). FSL constructs are water dispersible and consist of three components; a F functional head group, a S spacer and a L diacyl lipid tail. This technology allows users to introduce novel antigen profiles or characteristics at the membrane surface of cells. Methods: FSL constructs were synthesised bearing carbohydrates, peptides, and fluorophores. One part (0.05 ml) of FSL construct 1 mg/ml and one part of packed red cells were combined, mixed and incubated at 37°C for 2 hours, washed and then analysed for the presence of constructs by direct-indirect agglutination and fluorescence serological methods. Results: In all cases red cells were shown to be able to be precisely labelled with serologically detectable FSL construct. Red cells were modified to carry ABO, H, Lewis, acquired-B, the animal antigen Galili, hyaluronic acid, fluorophores and blood group peptides (Miltenberger). Conclusion: FSL cell surface coating technology allows for the creation of red cells expressing controlled levels of normal and/or novel antigens or structures. Such cells can be used for quality control, specialised antibody screening and identification panels and have potential for novel future applications.